Implementation of process technology and diversification of Astiri Oil products to improve community economy - Marisca Evalina Gondokesumo; Azminah Azminah; Bobby Ardiansyahmiraja; Dwie Retna Suryaningsih (University of Merdeka Malang, 2025)
Jatijejer Village, located between the slopes of Mount Penanggungan and Mount Welirang, has significant potential for cultivating aromatic plants, particularly lemongrass (Cymbopogon citratus) and citronella (Cymbopogon nardus). These plants are sources of essential oils with various benefits, including uses in aromatherapy, antibacterial, and anti-inflammatory applications, and are widely utilized in the cosmetics and healthcare industries. Despite this potential, the community of Jatijejer Village previously only utilized lemongrass as raw material, yielding suboptimal economic value and welfare improvement. This community service program aims to enhance the welfare of Jatijejer Village through the production and diversification of essential oil-based products. Activities included training in steam distillation techniques, quality measurement of essential oils, and the development of derivative products such as inhalers and diffusers. Evaluation results showed a significant improvement in participants' knowledge and skills. The average pre-test score of 58.4 percent increased to 97.2 percent in the post-test. Additionally, the essential oils produced were successfully developed into value-added products, such as inhalers and diffusers, which have begun to be marketed locally. Solid waste from the distillation process was also utilized as organic fertilizer, reinforcing the program's sustainability. This training effectively improved the skills, income, and economic independence of the Jatijejer Village community.